Bacteriology of deep neck infections: analysis of 634 patients. (19th May 2015) - Celakovsky, P; Kalfert, D; Smatanova, K; Tucek, L; Cermakova, E; Mejzlik, J; Kotulek, M; Vrbacky, A; Matousek, P; Stanikova, L; Hoskova, T
Abstract: Background: The aim of this study was to review the bacteriology of deep neck infections (DNI) and identify the factors that influence the incidence of causative bacteria. Methods: A retrospective analysis of 634 patients with DNI was performed. Statistical analysis was used to compare the incidence of common pathogens in various conditions such as age of the patients, aetiology and associated diabetes mellitus. Results: Bacteria were isolated in 514 cultures (81%). Aerobic bacteria were isolated from 246 cultures (39%) and anaerobic bacteria from 61 cultures (10%). Both aerobic and anaerobic bacteria were isolated from 207 cultures (32%). The most common aerobic bacteria were Streptococcus pyogenes (41%) and Staphylococcus aureus (32%). The most common anaerobic bacteria were Peptostreptococcus species (28%), followed by Prevotela species (8%) and Proprionibacterium species (7%). The incidence of anaerobic bacteria was higher in adults, in patients with infections of dental origin and in non‐diabetic patients. Conclusions: The bacteriology of DNI is polymicrobial, including both aerobic and anaerobic bacteria. The incidence of anaerobic bacteria is higher in adults, in patients with infections of dental origin and in non‐diabetic patients.